Resource Partitioning between Bacteria, Fungi, and Protists in the Detritusphere of an Agricultural Soil - Kramer, Susanne; Dibbern, Dörte; Moll, Julia; Huenninghaus, Maike; Koller, Robert; Krueger, Dirk; Marhan, Sven; Urich, Tim; Wubet, Tesfaye; Bonkowski, Michael; Buscot, François; Lueders, Tillmann; et al. (Frontiers in Microbiology, 2016)
The flow of plant-derived carbon in soil is a key component of global carbon cycling. Conceptual models of trophic carbon fluxes in soil have assumed separate bacterial and fungal energy channels in the detritusphere, controlled by both substrate complexity and recalcitrance. However, detailed understanding of the key populations involved and niche-partitioning between them is limited. Here, a microcosm experiment was performed to trace the flow of detritusphere C from substrate analogues (glucose, cellulose) and plant biomass amendments (maize leaves, roots) in an agricultural soil. Carbon flow was traced by rRNA stable isotope probing and amplicon sequencing across three microbial kingdoms. Distinct lineages within the Actinobacteria, Bacteroidetes, Gammaproteobacteria, Basidiomycota, Ascomycota as well as Peronosporomycetes were identified as important primary substrate consumers. A dynamic succession of primary consumers was observed especially in the cellulose treatments, but also in plant amendments over time. While intra-kingdom niche partitioning was clearly observed, distinct bacterial and fungal energy channels were not apparent. Furthermore, while the diversity of primary substrate consumers did not notably increase with substrate complexity, consumer succession and secondary trophic links to bacterivorous and fungivorous microbes resulted in increased food web complexity in the more recalcitrant substrates. This suggests that rather than substrate-defined energy channels, consumer succession as well as intra- and inter-kingdom cross-feeding should be considered as mechanisms supporting food web complexity in the detritusphere.